From Which to Why Not Religions in the Curriculum. A Troubled Pedagogy - Bekithemba Dube (E-Journal of Religious and Theological Studies)
The theoretical paper tapped into Bernstein’s notion of weak framing to point out the ambivalence of the religious curriculum in Zimbabwe. It showed the curriculum terrain that Religious Education has undergone and predicted its future. It also showed how curriculum conversations have moved the “which religions” question to why not religions in the curriculum. The paper argued that the weak framing of the religious curriculum presents itself as a playing field for politicians, curriculum planners, and educators where its validity is not to benefit the learners but to push the propaganda of the ZANU PF regime. The paper concludes, arguing that the presence of the religious curriculum has always been to buttress the status quo of the oppressor and the oppressed. Rejuvenation of the field is necessary, and urgent so that learners are not deprived of the benefits associated with the RE curriculum.